2015
DOI: 10.2169/internalmedicine.54.2736
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Alcohol Intake and Risk Factors for Metabolic Syndrome in Men

Abstract: Objective The precise relationship between alcohol intake and metabolic syndrome (MetS) is still unclear, and the results from previous studies have been inconclusive. Thus, we examined the effect of alcohol intake on the risk of MetS in men in order to gain more information on a potential relationship. Methods This study included 22,349 men who were divided into four groups according to their average alcohol intake [non-, light (less than 20 g ethanol/day), heavy (equal or more than 20 g and less than 60 g et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…Abdominal visceral fat may accumulate due to an imbalance between energy intake and expenditure. Unhealthy lifestyle behaviors such as fast eating ( 9 - 11 ), skipping breakfast and having late-night meals ( 12 ), heavy drinking ( 11 , 13 , 14 ), smoking ( 11 , 14 , 15 ), and lacking regular exercise or a low physical activity ( 11 , 15 , 16 ) have been associated with an increased risk of MetS. A Japanese government survey revealed that the prevalence of MetS and preMetS increases with age, and both are more predominant in men over all generations ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Abdominal visceral fat may accumulate due to an imbalance between energy intake and expenditure. Unhealthy lifestyle behaviors such as fast eating ( 9 - 11 ), skipping breakfast and having late-night meals ( 12 ), heavy drinking ( 11 , 13 , 14 ), smoking ( 11 , 14 , 15 ), and lacking regular exercise or a low physical activity ( 11 , 15 , 16 ) have been associated with an increased risk of MetS. A Japanese government survey revealed that the prevalence of MetS and preMetS increases with age, and both are more predominant in men over all generations ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…We also found out that alcohol drinking was positively associated with waist circumference, which could be due to the fact that alcohol increases central obesity as it contributes to the energy pool of the body 33,34 . There was also a significant positive association between sleep hours and HDL level and negative association with LDL level.…”
Section: Discussionmentioning
confidence: 63%
“…A reduction in the concentrations of free fatty acids in plasma results in a decrease in body weight (48) . Studies so far on food and the microbiome have mainly focused on meat-based/plant-based diet and highlighted differences in the microbiota of plant-and animal-based diets (47,49,(50)(51)(52) . In particular, they have demonstrated that human gut responds rapidly to major dietary changes (53) .…”
Section: Microbiomementioning
confidence: 99%